Low Equivalent Oxide Thickness and Leakage Current of pGe MOS Device by Removing Low Oxidation State in GeOx With H2 Plasma Treatment - Ruan, Dun-Bao; Chang-Liao, Kuei-Shu; Yi, Shih-Han; Yeh, Hsin-I; Liu, Guan-Ting (IEEE electron device letters, 2020)
A low equivalent-oxide-thickness of 0.58 nm and a low gate leakage current density of \sim 2× 10^{-{5}} A/cm 2 at V G = V FB - 1 V in p-substrate Ge (pGe) MOS device can be simultaneously achieved by a hydrogen plasma (H * ) treatment on GeO 2 interfacial layer (IL). It is found that the removal of GeO x with low oxidation state in GeO 2 IL play crucial roles on electrical characteristics of pGe MOS device. Through a H * treatment, the electrical and reliability characteristics are improved by a GeO 2 IL with high oxidation state. Therefore, a GeO 2 IL with H * treatment is promising for high performance pGe MOS devices.